Synthesis, biological and computational evaluation of novel cyanomethyl vinyl ether derivatives - Martín-Encinas, Endika; Fuertes, María; Delgado-Hernández, Samuel; García-Tellado, Fernando; Tejedor, David; Alonso, Concepción (Frontiers in Pharmacology, 2024)
This work explores the biological evaluation of novel cyanomethyl vinyl ether derivatives as antiproliferative agents. Tubulin, crucial to microtubule structure and function, is a target for cancer therapies. In vitro cytotoxicity assessments revealed significant activity in SKOV3 ovarian carcinoma cells and A549 lung carcinoma cells. Structure-Activity Relationship (SAR) analysis indicated that the E isomer and specific substitutions influenced the biological activity. Computational assays predicted favorable ADME properties, highlighting potential as anticancerous agents. Molecular docking studies demonstrated that compound 12E, with the E geometry of the double bond and fused polyaromatic rings such as phenanthrene, has robust interaction with tubulin, suggesting enhanced stability due to diverse amino acid interactions. Comparative spatial distributions with colchicine further indicated potential mechanistic similarities.